2022
DOI: 10.3171/2022.1.jns212096
|View full text |Cite
|
Sign up to set email alerts
|

Representation of female neurosurgeons as abstract authors at neurological surgery conferences

Abstract: OBJECTIVE Female neurosurgeon representation has increased, but women still represent only 8.4% of neurosurgeons in the US. Women are significantly underrepresented as authors in neurosurgical and spine journals, a key indicator of professional success in academic medicine. In this study, the authors aimed to assess the gender diversity of first and last authors of accepted abstracts at neurosurgical conferences in 2015 and 2019. METHODS Annual meeting abstracts for 2015 and 2019 of the American Association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…all medical fields, 11,19 our findings do echo those noted in plastic surgery and dermatologic surgery. 20,21 Our hypothesis that larger gender disparities would be present between the neurosurgical authors than the otolaryngology authors was correct.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 4 more Smart Citations
“…all medical fields, 11,19 our findings do echo those noted in plastic surgery and dermatologic surgery. 20,21 Our hypothesis that larger gender disparities would be present between the neurosurgical authors than the otolaryngology authors was correct.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…This is noteworthy, given a recent study of first and last authors presenting at two major neurosurgery conferences found no significant change in female authorship rates from 2015 to 2019. 11 That study, unlike ours, used presenting author as a surrogate to determine first author. It also coded gender via "traditional naming conventions" and, if names appeared ambiguous to the researchers, internet search.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations